Risk assessment methodology: implementation of duration gap in corporate portfolios in order to reduce the systemic risk (2018)
In this article we propose a new methodology for measuring companies with financial risk exposure, based on the concept of duration in assets and liabilities management that can be applied in corporate portfolios. Risk indicators in banks usually try to measure the dynamic of accounts in the income statement and capital levels. With this research, we demonstrate how the methodology can be applied from banks to any company or industry sector. Then, we compare the methods for managing accounts in financial institutions and also identifying their adaptability to any type of corporation. We also made a comparison between the management elements used in financial markets and organizations assets, verifying their adaptability level. Finally, we present a real case study.